2006
DOI: 10.1243/095765006x76036
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of three-dimensional flow in a centrifugal fan volute with large volute width and rectangular cross-section

Abstract: Among all the elements of a centrifugal fan, the volute is the one that has the lowest flow efficiency. Therefore, improving the performance of the volute is an efficient way to improve the total performance of a centrifugal fan. To contribute a better understanding of the flow structure in the fan volute, the three-dimensional flow in a centrifugal fan volute with a large volute width and rectangular cross-section has been measured in detail by means of five-hole probe at three different flowrates. The time-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Fan noise can generally be reduced by increasing the spiral line of the volute or enlarging the blade-tongue gap, which diminishes the fluiddynamic loading on the volute and the magnitude of tonal noise. 1,2 The pressure pulsation due to the flow impact of the volute tongue through the impeller-exit and the source region can be easily diagnosed. 3 Correct matching of the impeller and volute plays an important role in the centrifugal fan design process.…”
Section: Introductionmentioning
confidence: 99%
“…Fan noise can generally be reduced by increasing the spiral line of the volute or enlarging the blade-tongue gap, which diminishes the fluiddynamic loading on the volute and the magnitude of tonal noise. 1,2 The pressure pulsation due to the flow impact of the volute tongue through the impeller-exit and the source region can be easily diagnosed. 3 Correct matching of the impeller and volute plays an important role in the centrifugal fan design process.…”
Section: Introductionmentioning
confidence: 99%
“…1 The efficiency of volutes, however, is the lowest among all components of the centrifugal fan. 2 Dawes 3 pointed out the fact that almost two-thirds of the energy losses occurred in the diffuser of the centrifugal compressor.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, many investigations have observed that the actual flow at the impeller inlet is non-uniform and the flow in each flow passage is different due to the asymmetric volute geometry, which induces the pressure grades along the circumferential direction. [4][5][6][7][8] The above impeller-volute interaction is an important cause of the flow separation and the reversed flow in the flow passage, and it also increases the flow loss and the noise level. Many research works indicate that improving the inlet condition of the impeller is an effective way to reduce the noise of fans.…”
Section: Introductionmentioning
confidence: 99%